2023
DOI: 10.1111/1365-2745.14112
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality regulates the structure and biogeochemical impact of ectomycorrhizal fungal communities across environmentally divergent neotropical dry forests

Abstract: Ectomycorrhizal (ECM) symbioses support forest functioning globally, yet both the structure and function of ECM fungal communities in seasonally dry neotropical forests (SDTFs), known for extreme heterogeneity in vegetation and edaphic properties, remain under characterized. Here, we evaluated the relative influences of seasonal versus spatial variation in ECM fungal community structure in soils from four environmentally divergent SDTFs. We also assessed the importance of biotic and abiotic drivers of SDTF ECM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 163 publications
0
3
0
Order By: Relevance
“…A study in Austria found no Populus tremula- associated EcM taxa that were significantly associated with summer or autumn conditions ( Krpata et al, 2008 ). Yet many studies have found significance of seasonal factors on fungal relative abundance ( Zhao et al, 2023 ) and community compositions ( Vargas-Gastélum et al, 2015 ; Beidler et al, 2023 ). Others have suggested that host-tree characteristics have more impact than the seasonal factor alone in describing changes in fungal communities ( Park et al, 2020 ), thus the seasonal factor should be considered in interaction with tree or site characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Austria found no Populus tremula- associated EcM taxa that were significantly associated with summer or autumn conditions ( Krpata et al, 2008 ). Yet many studies have found significance of seasonal factors on fungal relative abundance ( Zhao et al, 2023 ) and community compositions ( Vargas-Gastélum et al, 2015 ; Beidler et al, 2023 ). Others have suggested that host-tree characteristics have more impact than the seasonal factor alone in describing changes in fungal communities ( Park et al, 2020 ), thus the seasonal factor should be considered in interaction with tree or site characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…4 and 6 ). The relative abundance of ectomycorrhizal fungi typically increases during seasons with high photosynthetic activity ( 20 , 35 , 81 ), likely explaining why relative abundance of these fungi was greatest during summer ( Fig. 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…This evidence presents the possibility that tree microbiomes change continuously over time, causing seasonal fluctuations and longer-term shifts to occur simultaneously. However, studies of intra-annual variation in the composition of tree microbiomes typically span a single year ( 20 , 35 37 ). Consequently, it has remained challenging to disentangle seasonal variation from longer-term shifts in tree-associated microbial communities, as well as from numerous climatic, edaphic, and host genotypic differences that correlate with spatial variation in the composition of plant microbiomes ( 37 42 ).…”
Section: Introductionmentioning
confidence: 99%